The necessary training needs for the Arabic language teachers in the basic stage as estimated by the educational directorates in Al-Mafraq Governate - Hamadnah, Adeeb (Jordan Journal of Educational Sciences, 2007)
This study aimed at identifying the Arabic teachers training needs in the basic stage as estimated by teachers in the Educational Directorates in Al- Mafraq Governorate. The sample of the study consisted of 135 male and female teachers. The instrument consisted of sixty items divided into eight areas. The SPSS was used to analyze the data. The results of the study revealed that there was a slight degree of lack in the following areas: evaluation, language internalization, instructional technology and computer technology. The study also revealed that there was a moderate need in the following areas: teaching methods class management, lesson planning, communication with student’s parents, and curriculum analysis. The results also showed no statistical difference (α= 0.05) attributed to scientific qualification and the place of work in favor of the North Eastern Batra. The study presented some recommendations in the light of the results.